Pengaruh Perhatian Orang Tua dan Motivasi Berprestasi terhadap Prestasi Belajar Fisika - Siwi Puji Astuti; Santy Handayani (Universitas Indraprasta PGRI Jakarta, 2017)
The research is aimed at showing the effects of parental attention and achievement motivation on physics learning achievement. The hypotheses are 1) there are joint effects of parental attention and achievement motivation on physics learning achievement, 2) there is an effect of parental attention on physics learning achievement, 3) there is an effect of achievement motivation on physics learning achievement. The method used in this research is a survey method with multiple regression analysis. The population is students of class XI IPA of 2016/2017 school year in SMA Negeri in Kramat Jati, with 74 students from 2 SMA Negeri taken as the sample by applying the random sampling technique. The data are collected by distributing questionnaires and examining first-semester reports. The technique used in the data analysis is multiple regression F-Test and T-test. The data requirement test includes five classic assumption tests. In conclusion, the data analysis result shows that 1) there are joint effects of parental attention and achievement motivation on physics learning achievement, as proven by the value of Sig = 0.000 and FObserved = 17.953, 2) there is an effect of parental attention on the physics learning achievement, as proven by the value of Sig = 0.037 and tObserved = 2.125 and 3) there is an effect of achievement motivation on physics learning achievement, as proven by the value of Sig = 0.000 and tObserved = 5.053.